2009
DOI: 10.1080/10715760902918683
|View full text |Cite
|
Sign up to set email alerts
|

Expression of NADPH oxidase homologues and accessory genes in human cancer cell lines, tumours and adjacent normal tissues

Abstract: The family of NADPH oxidase (NOX) genes produces reactive oxygen species (ROS) pivotal for both cell signalling and host defense. To investigate whether NOX and NOX accessory gene expression might be a factor common to specific human tumour types, this study measured the expression levels of NOX genes 1-5, dual oxidase 1 and 2, as well as those of NOX accessory genes NoxO1, NoxA1, p47 phox , p67 phox and p22 phox in human cancer cell lines and in tumour and adjacent normal tissue pairs by quantitative, real-ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
156
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 135 publications
(169 citation statements)
references
References 37 publications
(43 reference statements)
11
156
1
1
Order By: Relevance
“…38,39 Moreover, a microarray analysis indicated that Noxo1 expression is upregulated in a subpopulation of colon cancers. 40 Accordingly, it is possible that Noxo1 is induced in cancer cells, together with NOX1, in the inflammatory microenvironment, contributing to an oncogeneinduced transformation phenotype through the generation of reactive oxygen species.…”
Section: Discussionmentioning
confidence: 99%
“…38,39 Moreover, a microarray analysis indicated that Noxo1 expression is upregulated in a subpopulation of colon cancers. 40 Accordingly, it is possible that Noxo1 is induced in cancer cells, together with NOX1, in the inflammatory microenvironment, contributing to an oncogeneinduced transformation phenotype through the generation of reactive oxygen species.…”
Section: Discussionmentioning
confidence: 99%
“…Although at high concentrations ROS can be cytotoxic, physiologic ROS levels play a critical role in the control of tumor cell growth, differentiation, and signal transduction (7). Although ROS are primarily a by-product of aerobic metabolism in mammalian cells, the recently discovered family of epithelial NADPH oxidases (reduced nicotinamide adenine dinucleotide phosphate oxidases (Noxs)), contributes significantly to intracellular ROS production in tumor cells (8,9). Dual oxidase 2 (Duox2) belongs to the Nox family of oxidases that is composed of six additional enzymes, including Nox1-5 and dual oxidase 1 (Duox1) (10).…”
mentioning
confidence: 99%
“…Elevated levels of lipid rafts have been reported in breast cancer cells (27). Recently, expression of Nox isoforms (Nox1-5) has been reported in some breast cancer cell lines, including MCF-7 (46). Therefore, we speculated that there is an association between lipid rafts and NADPH oxidases in breast cancer cells.…”
Section: Discussionmentioning
confidence: 95%